Tooth retention, health, and quality of life in older adults: a scoping review - Adejare Jay Atanda; Alicia A. Livinski; Steven D. London; Shahdokht Boroumand; Darien Weatherspoon; Timothy J. Iafolla; Bruce A. Dye (BMC Oral Health, 2022)
Abstract Objective This scoping review describes the relationship between tooth retention, health, and quality of life in older adults. Methods Seven databases were searched for English language articles for subjects ≥ 65 y from 1981 to 2021. Exposure was tooth retention (≥ 20), and outcomes were general/systemic health and quality of life. Methodological quality was assessed using the Newcastle–Ottawa Scale and Cochrane Risk of Bias 2.0 tool. Results 140 articles were included, only four were randomized trials. Inter-rater agreement (κ) regarding study inclusion was 0.924. Most were assessed with low risk of bias (n = 103) and of good quality (n = 96). Most studies were conducted in Japan (n = 60) and Europe (n = 51) and only nine in the US. Tooth retention was referred to as “functional dentition” in 132 studies and “shortened dental arch” in 19 studies. Study outcomes were broadly synthesized as (1) cognitive decline/functional dependence, (2) health status/chronic diseases, (3) nutrition, and (4) quality of life. Discussion There is a positive relationship between tooth retention, overall health, and quality of life. Older adults retaining ≥ 20 teeth are less likely to experience poorer health. Having < 20 teeth increases the likelihood for functional dependence and onset of disability, and may affect successful ageing. This review supports the general finding that the more teeth older adults retain as they age, the less likely they are to have adverse health outcomes. However, significant knowledge gaps remain which can limit decision-making affecting successful ageing for many older adults. This review highlights the need to consider, as an important marker of oral health and function, the retention of a functional minimum of a natural dentition, rather than a simple numeric score of missing teeth.